Penetrating buttock trauma: A life‐threatening injury that highlights the importance of good collaboration with trauma receiving hospitals. Issue 8 (9th August 2022) - Angelou, Dimitrios; McKeever, Mark; Doran, Amy; Malik, Momin
Abstract: A 54‐year‐old lady was brought to our emergency department after falling from a stepladder onto the base of her artificial Christmas tree. The metallic rod impaled her through the right buttock. X‐rays and a computerized tomography were performed prior to transport to a trauma center causing delays to her surgery. Abstract : Penetrating buttock trauma should be considered a life‐threatening injury and bleeding is the primary concern for mortality (1, 2). Consequently, prompt transfer to trauma centers should be arranged for definitive management without delays for scans.